Don't solve this equation, please!

Algebra Level 5

The equation ( x 2 9 ) ( x 3 9 ) ( x 4 9 ) ( x 10 9 ) = 1 \left(x-\sqrt[9]{2}\right)\left(x-\sqrt[9]{3}\right)\left(x-\sqrt[9]{4}\right)\ldots\left(x-\sqrt[9]{10}\right)=1 has 9 distinct complex solutions x 1 , x 2 , x 3 , , x 9 x_1,x_2, x_3, \ldots,x_9 . Find the value of x 1 9 + x 2 9 + x 3 9 + + x 9 9 x_1^9+x_2^9+x_3^9 + \ldots+x_9^9 .


The answer is 63.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

X X
Jul 2, 2018

Relevant wiki: Vieta's Formula Problem Solving - Intermediate

Let the roots of the equation x 9 + m 1 x 8 + m 2 x 7 + m 3 x 6 + m 4 x 5 + m 5 x 4 + m 6 x 3 + m 7 x 2 + m 8 x + m 9 = 0 x^9+m_1x^8+m_2x^7+m_3x^6+m_4x^5+m_5x^4+m_6x^3+m_7x^2+m_8x+m_9=0 be a 1 , a 2 , a 3 . . . a 9 a_1,a_2,a_3...a_9 .

Then a 1 a 2 a 3 . . . a 9 = m 9 a_1a_2a_3...a_9=-m_9 ,and a 1 9 + a 2 9 + a 3 9 + . . . + a 9 9 = f 9 ( m 1 , m 2 , m 3 , . . . m 8 ) + n m 9 a_1^9+a_2^9+a_3^9+...+a_9^9=f_9(m_1,m_2,m_3,...m_8)+nm_9 where f 9 f_9 is some function,and n n is a constant.


Let's find n n first.Consider the equations x 9 = 0 x^9=0 and x 9 1 = 0 x^9-1=0 .

The first equation's roots are b 1 , b 2 , b 3 , . . . b 9 b_1,b_2,b_3,...b_9 ,and the second one's are c 1 , c 2 , c 3 , . . . c 9 c_1,c_2,c_3,...c_9

According to the above,we have b 1 9 + b 2 9 + b 3 9 + . . . + b 9 9 = 0 = f 9 ( 0 , 0 , 0 , . . . , 0 ) + 0 n b_1^9+b_2^9+b_3^9+...+b_9^9=0=f_9(0,0,0,...,0)+0n and c 1 9 + c 2 9 + c 3 9 + . . . + c 9 9 = 9 = f 9 ( 0 , 0 , 0 , . . . , 0 ) 1 n c_1^9+c_2^9+c_3^9+...+c_9^9=9=f_9(0,0,0,...,0)-1n

So we get n = 9 n=-9


Consider the 2 equations ( x 2 9 ) ( x 3 9 ) ( x 4 9 ) ( x 10 9 ) 1 = 0 \left(x-\sqrt[9]{2}\right)\left(x-\sqrt[9]{3}\right)\left(x-\sqrt[9]{4}\right)\ldots\left(x-\sqrt[9]{10}\right)-1=0 and ( x 2 9 ) ( x 3 9 ) ( x 4 9 ) ( x 10 9 ) = 0 \left(x-\sqrt[9]{2}\right)\left(x-\sqrt[9]{3}\right)\left(x-\sqrt[9]{4}\right)\ldots\left(x-\sqrt[9]{10}\right)=0 Expand them,and they will be in the form of x 9 + p 1 x 8 + p 2 x 7 + p 3 x 6 + p 4 x 5 + p 5 x 4 + p 6 x 3 + p 7 x 2 + p 8 x 10 ! 9 1 = 0 x^9+p_1x^8+p_2x^7+p_3x^6+p_4x^5+p_5x^4+p_6x^3+p_7x^2+p_8x-\sqrt[9]{10!}-1=0 and x 9 + p 1 x 8 + p 2 x 7 + p 3 x 6 + p 4 x 5 + p 5 x 4 + p 6 x 3 + p 7 x 2 + p 8 x 10 ! 9 = 0 x^9+p_1x^8+p_2x^7+p_3x^6+p_4x^5+p_5x^4+p_6x^3+p_7x^2+p_8x-\sqrt[9]{10!}=0 where p 1 , p 2 , . . . , p 8 p_1,p_2,...,p_8 are constants.

According to the above,we have x 1 9 + x 2 9 + x 3 9 + . . . + x 9 9 = f 9 ( p 1 , p 2 , p 3 , . . . , p 8 ) + 9 ( 10 ! 9 + 1 ) x_1^9+x_2^9+x_3^9+...+x_9^9=f_9(p_1,p_2,p_3,...,p_8)+9(\sqrt[9]{10!}+1) and 2 + 3 + 4 + . . . + 10 = 54 = f 9 ( p 1 , p 2 , p 3 , . . . , p 8 ) + 9 10 ! 9 2+3+4+...+10=54=f_9(p_1,p_2,p_3,...,p_8)+9\sqrt[9]{10!}

Subtract and get x 1 9 + x 2 9 + x 3 9 + . . . + x 9 9 = 63 x_1^9+x_2^9+x_3^9+...+x_9^9=\boxed{63}


To get a clearer idea about expressing a 1 9 + a 2 9 + a 3 9 + . . . + a 9 9 a_1^9+a_2^9+a_3^9+...+a_9^9 in the form of f 9 ( m 1 , m 2 , m 3 , . . . m 8 ) + n m 9 f_9(m_1,m_2,m_3,...m_8)+nm_9 ,here is an example of a third degree one.

If the equation x 3 + p x 2 + q x + r = 0 x^3+px^2+qx+r=0 has roots a , b , c a,b,c ,then

a 3 + b 3 + c 3 = ( a + b + c ) 3 3 ( a + b + c ) ( a b + b c + c a ) + 3 a b c = p 3 + 3 p q 3 r a^3+b^3+c^3=(a+b+c)^3-3(a+b+c)(ab+bc+ca)+3abc=-p^3+3pq-3r If f 3 ( x , y ) = x 3 + 3 x y , m = 3 f_3(x,y)=-x^3+3xy,m=-3 ,then a 3 + b 3 + c 3 a^3+b^3+c^3 can be expressed in the form of f 3 ( p , q ) + m r f_3(p,q)+mr

If we generalise, then the answer for arbitrary n n comes out to be n ( n + 5 ) 2 \frac{n\left(n+5\right)}{2} . In simpler terms,

If x 1 , x 2 , x 3 . . . . . x n x_{1}\ ,\ x_{2}\ ,\ x_{3}\ .....\ x_{n} are roots of the equation ( x 2 n ) ( x 3 n ) ( x 4 n ) . . . . . ( x n + 1 n ) = 1 \left(x-\sqrt[n]{2}\right)\left(x-\sqrt[n]{3}\right)\left(x-\sqrt[n]{4}\right).....\left(x-\sqrt[n]{n+1}\right)=1

Then, x 1 n + x 2 n + x 3 n + . . . . . x n n = n ( n + 5 ) 2 x_{1}^{n}+\ x_{2}^{n}+x_{3}^{n}+.....\ x_{n}^{n}\ =\ \frac{n\left(n+5\right)}{2}

Aaghaz Mahajan - 1 year ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...